2009 Canadian Association of Gastroenterology Educational Needs Assessment Report. (2009) - Rostom, Alaa; Daniels, Sandra
Abstract : The annual survey of Canadian Association of Gastroenterology (CAG) members' educational needs was conducted via an online survey during April 2009. A total of 261 individuals completed the survey. Similar to previous years, inflammatory bowel disease (IBD) topics – particularly Crohn's disease and ulcerative colitis (UC) therapeutics, and difficult IBD cases – were most in demand for future educational events. Other highly rated areas were endoscopic techniques and therapeutics, celiac disease, approach to gastrointestinal (GI) infections and live endoscopy. The two most popular educational formats were 'Lectures/presentations streamed to computer/podcasts' and 'A CAG educational portal to on-line presentations, self-assessments and maintenance of certification (MainCert) point tracking'.